Correction to: Optimizing conditions for labeling of mesenchymal stromal cells (MSCs) with gold nanoparticles: a prerequisite for in vivo tracking of MSCs - Nold, Philipp; Jungebluth, Philipp (Journal of nanobiotechnology, 2019)
The authors apologized for the unfortunate error in figure during publication of the article and they also explained that some of the solid grey graphs in Fig. 5 are intentionally based on the same data. For 8 different surface makers (CD14, CD73, CD34, CD105, CD19, CD90, CD45, HA-DR) in accordance to the guidelines of the manufacturer a panel of 4 different isotype controls were used, corresponding to 4 different fluorescence channels.
Gesehen am 04.12.2019